Assistive Eyewear: Arduino Powered Eyeglasses for Blind Individuals - Fernandez, Jane Motas; valencia, armie; daniel, villano; Cunanan, Delbert Carlos D (IC-ITECHS, 2024)
The quality of life for individuals with visual impairments has been significantly enhanced by assistive technologies. This paper introduces a new solution called Arduino Powered Eyeglasses (APE) for Blind Individuals tailored specifically for blind individuals. APE integrates sophisticated sensors, microcontrollers, and audio feedback systems into a wearable device, enhancing spatial awareness and navigation capabilities. Utilizing ultrasonic sensors, the system detects obstacles in the user's path and delivers real-time audio feedback through a buzzer embedded in the eyeglasses frame. Furthermore, it has an embedded vibration motor that acts as a feedback system as well when navigating an outdoor and indoor environment that is noisy. The design, implementation, and preliminary evaluation of APE are presented herein, emphasizing its effectiveness in aiding blind individuals with various daily tasks and promoting independence and mobility. APE's affordability and user-friendly interface position it as a promising solution for empowering individuals with visual impairments to navigate the world with increased confidence and autonomy.